Perfil dos profissionais da rede de educação especial: descrição da formação e do conjunto de processos e práticas na educação superior - Vestena, Natana Pozzer (2017)
In the present scenario, that many institutions are guaranteeing the access of students with disabilities through quota reservation, it is necessary to investigate "who" (in the space and action provided to him) and "how" (processes and practices), it has been guaranteeing the permanence and conclusion of students with disabilities in Higher Education. The present research aims to analyze the profile of the professional who works in the accessibility center work group, against the aid to specific educational needs of the disabled student in a Federal Institution of Higher Education. The research took place in an institution in Rio Grande do Sul, which, until 2016, opted for the vacancies reservation (quotas) for people with disabilities. From a qualitative approach, this research is delineated as a single, exploratory-descriptive case study and obtains its data through a questionnaire, an interview and documents, in order to achieve its specific objectives. In the analysis of the data collected, it is used the technique of Content Analysis (Bardin, 2011), with a priori categories established and others according to the analysis. In order to base on the theoretical contribution, the authors of the Education and Special Education area were used, such as Antunes (2014), Perrenoud (2010), Demo (2012), Carvalho (2011), Januzzi (2012) and Rogers (1951; 1961, 1985), as well as legislation, which often constitutes the existing educational context, and provides (re) think others, such as Higher Education. It is concluded that concerning to policies, laws, decrees, there is nothing specifically defined for the inclusion of students with disabilities in Higher Education, place or type of care and professional to perform aid. Regarding the team of the Accessibility Center, there are three members, among them, the Educational Technician who performs the care of these students, that the demands are the most diverse. Concerning to services, practices, processes and resources, many were instituted according to the needs of the students. In relation to the graduation of this civil servant, the skills and more specific competences to aid to the intellectual handicapped are noticed, however, in continuous training other skills and competences in the Special Education area are developed and also realizes with the importance, mainly, of empathy, positive unconditional consideration, congruence and authenticity on the part of the professional towards the student, and also the importance of developing all these in the aid for the student. One of the practices also constituted as a service, as initial idea such the Basic Education, but with reformulations, is the Specialized Educational Attendance which demonstrates to guarantee the permanence of students with deficiency in Higher Education. It is concluded, regarding to all the results, the need to establish a team with several professionals, and within this group of professionals from the same area, such as Special Education, but with different skills and competences. However, it is still investment in policies or internal regulations that address minimally the attendance of the specific educational needs, and other orientations for these students and professionals in such context, nationally and institutionally considering the local specificities.